2008
DOI: 10.1111/j.1365-2249.2008.03605.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant early secreted antigen target 6 protein as a skin test antigen for the specific detection of Mycobacterium tuberculosis infection

Abstract: SummaryAlthough the delayed-type hypersensitivity skin test reaction to tuberculin purified protein derivative (PPD) is used worldwide for tuberculosis (TB) detection, it is incapable of distinguishing Mycobacterium tuberculosis (MTB) infection from bacille Calmette-Guérin (BCG) vaccination or infection with non-tuberculous Mycobacteria. As a result, there is an urgent need for a more specific diagnostic tool for TB. This study reports the skin reactions of guinea pigs and human volunteers to recombinant early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 16 publications
5
14
0
Order By: Relevance
“…Animal experiments showed that the PPD skin test was positive in BCG- and M. tuberculosis -sensitized guinea pigs, and the rESAT6 skin test was negative in BCG-sensitized guinea pigs and positive in M. tuberculosis -sensitized guinea pigs. The experiments indicated that the rESAT6 skin test was able to be used to make the differential diagnosis between BCG vaccination and M. tuberculosis infection, which was consistent with findings of other studies [2225]. …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Animal experiments showed that the PPD skin test was positive in BCG- and M. tuberculosis -sensitized guinea pigs, and the rESAT6 skin test was negative in BCG-sensitized guinea pigs and positive in M. tuberculosis -sensitized guinea pigs. The experiments indicated that the rESAT6 skin test was able to be used to make the differential diagnosis between BCG vaccination and M. tuberculosis infection, which was consistent with findings of other studies [2225]. …”
Section: Discussionsupporting
confidence: 90%
“…M. marinum (ATCC927 strain) was used in our study, whereas the TMC1218 strain was used in the Wu study. In our study, the negative skin test result of rESAT6 protein might be the reason that the ESAT6 gene was incompletely expressed in the M. marinum strains [14,25]. Wu also demonstrated that the rESAT6 skin test was negative in the guinea pigs sensitized by M. smegmatis , M. fortuitum and M. phlei , as seen in our study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…ESAT-6 (Rv3875) and CFP10 (Rv3874), highly studied T-cell antigens that are absent in BCG, are currently used as reagents for the diagnosis of TB via an Interferon-gamma release assay (Mazurek, 2005;Chang & Leung, 2010). Recombinant ESAT-6 elicits a positive skin response in Mtb-infected guinea pigs and humans (Wu et al, 2008). Compared to the maximal DTH response at 72 h induced by PPD, the DTH response to ESAT-6 peaked 24 h later (Pollock et al, 2003).…”
Section: Pitfalls Of Ppdmentioning
confidence: 99%
“…This might especially be the case where the logistics of access to laboratorybased resources are problematic. It is also notable that in recent years, there has also been renewed interest in a skin test-based test for DIVA for human TB, with several reports demonstrating the skin test potential of ESAT-6 (1,3,28).…”
mentioning
confidence: 99%